2005
DOI: 10.1136/gut.2004.048298
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin/Eta-1 upregulated in Crohn's disease regulates the Th1 immune response

Abstract: Background and aims: The pathogenesis of Crohn's disease (CD), a chronic inflammatory bowel disease characterised by a Th1 immune response, remains unclear. Osteopontin (OPN) is a phosphoprotein known as an adhesive bone matrix protein. Recent studies have shown that OPN plays an important role in lymphocyte migration, granuloma formation, and interleukin 12 (IL-12) production. The present study investigated expression and the pathophysiological role of OPN in CD. Methods: Plasma OPN concentration was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
111
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(118 citation statements)
references
References 34 publications
4
111
0
1
Order By: Relevance
“…OPN plasma concentrations correlate with the severity of Crohn's disease, consistent with a role for OPN in Th1-mediated immune responses (Sato et al, 2005). OPN is anti-inflammatory in the acute phase but pro-inflammatory in the chronic phase of colitis.…”
Section: Dual Eeffectssupporting
confidence: 52%
“…OPN plasma concentrations correlate with the severity of Crohn's disease, consistent with a role for OPN in Th1-mediated immune responses (Sato et al, 2005). OPN is anti-inflammatory in the acute phase but pro-inflammatory in the chronic phase of colitis.…”
Section: Dual Eeffectssupporting
confidence: 52%
“…Dysregulated Opn expression has also been implicated in several autoimmune disorders, including murine experimental autoimmune encephalomyelitis (EAE) (8, 9), multiple sclerosis (10), rheumatoid arthritis (11), and atherosclerosis (12, 13). Dysregulated Opn expression has been correlated with excessive Th1 polarization of CD4 ϩ T cells in these disorders (7,14) opening the possibility that Opn gene expression may directly contribute to Th1͞type 1 CD8 ϩ T cells (Tc1) genetic programming. However, the genetic basis of Opn expression in Th-cell subsets is not well understood.…”
mentioning
confidence: 99%
“…Opn expression is also essential for effective Th1-dependent granuloma formation and a positive clinical outcome in patients suffering from mycobacterial infection (6), whereas ectopic Opn expression has been implicated in the granulomatous lesions of Crohn's disease (7). Dysregulated Opn expression has also been implicated in several autoimmune disorders, including murine experimental autoimmune encephalomyelitis (EAE) (8,9), multiple sclerosis (10), rheumatoid arthritis (11), and atherosclerosis (12,13).…”
mentioning
confidence: 99%
“…In CD, Gassler et al reported an elevated OPN expression in plasma cells, but not in epithelial cells [9]. Moreover, Sato et al observed an elevated plasma OPN and significant correlation with disease activity in CD, but not in UC [10].…”
mentioning
confidence: 99%
“…Several recent reports have suggested an important role for osteopontin (OPN) in the pathogenesis of IBD as well as its possible use as a biomarker [4][5][6][7][8][9][10]. Masuda et al demonstrated that expression of OPN is significantly elevated in the mucosa of patients with UC [6].…”
mentioning
confidence: 99%